Why do Malaysian Young Adults Buy Health Insurance? - Co-Nee Yeow; Lee-Ying Tay; Chun-Teck Lye; Eka Perwitasari Fauzi (Journal of International Business, Economics and Entrepreneurship)
The spread of the COVID-19 pandemic has amplified the importance of health insurance. Although most of the companies in Malaysia usually provide employee benefit plans such as medical coverage to their employees, the COVID-19 pandemic that severely impacted the economy and employment has also abruptly exposed the unemployed and retrenched workers to the risk of high medical costs. Thus, this study aims to identify the factors that affect the purchase intention of health insurance among Malaysian young adults in the transitional period of life and could be vulnerable to potentially catastrophic expenses in severe injury or illness. Using a convenience sampling method, a set of self-administered questionnaires was distributed to 200 young adults in Malaysia who are aged between 18 to 25 years old. The results show that attitude, perceived behavioural control, and perceived financial benefits significantly influence health insurance's purchase intention. This study offers an insight into the rationale of buying health insurance among Malaysian young adults, mainly from the behavioural perspective. The finding also suggests important managerial implications to the associated parties, particularly in reinforcing a positive attitude towards health insurance's purchase intention among Malaysian young adults.